SYSTEMIC INFLAMMATION, IMMUNE SYSTEM, LIPID PROFILE, AND ELECTROLYTE STATUS IN PATIENTS WITH ATRIAL FIBRILLATION AFTER COVID-19 - Sychov, O.S.; Stasyshena, O.V.; Talaieva, T.V.; Havrylenko, T.I.; Sribna, O.V.; Getman, T.V.; Marchenko, O.Ya. (World of Medicine and Biology, 2024)
Atrial fibrillation is the most common form of arrhythmia. Associated with significant morbidity and mortality in patients after suffering from COVID-19. The main group was formed of 116 people (64.8 %) with atrial fibrillation who suffered from a coronavirus infection. Control group 1 – 49 patients with atrial fibrillation who had no history of COVID-19 infection. Control group 2 – 22 patients with extrasystole who underwent COVID-19 but did not develop AF. Systemic inflammation, which occurs as a result of CI, provokes the appearance of de novo atrial fibrillation and worsening of the course of an already existing arrhythmia. Accompanied by an increase in the level of the N-terminal fragment of the brain natriuretic peptide precursor. There was no significant difference between the studied groups in the indicators of the level of electrolytes and lipoptotheids.